Worldview and spiritual search project: the ethos of practitioners of yoga and Vedanta Visão de mundo e projeto de busca espiritual: o ethos de praticantes do yoga e Vedanta - Bastos, Cecilia Guimarães (Revista de Antropologia, 2023)
I describe in this article the ethos of Brazilians studying Vedanta in India. To understand their experiences, I look into the Vedanta worldview, whose recurrent practices, especially meditation and yoga, accompanied by the study of sacred Hindu texts, are eventually embodied to their lifestyles. My analysis is based on the link between their ongoing studies in India and the significant transformations that occur not only in their lifestyle but also in their worldview. The purpose is to highlight the existence and meaning of some of these transformations, which might even cause a “paradigm shift” (a “native” category) – something so intense that it could lead them to reevaluate their deepest feelings. I, then, examine these transformations as consequences of their spiritual search projects.
Created from Fastlane, Scopus look-up
Keywords: Ethos; project; spiritual search; Vedanta; worldview